2003
DOI: 10.1096/fj.02-1115com
|View full text |Cite
|
Sign up to set email alerts
|

Bystander effect induced by counted high‐LET particles in confluent human fibroblasts: a mechanistic study

Abstract: The possible mechanism of a radiation-induced bystander response was investigated by using a high-LET heavy particle microbeam, which allows selected cells to be individually hit with precise numbered particles. Even when only a single cell within the confluent culture was hit by one particle of 40Ar (approximately 1260 keV/microm) or 20Ne (approximately 380 keV/microm), a 1.4-fold increase of micronuclei (MN) was detected demonstrating a bystander response. When the number of targeted cells increased, the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
72
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 34 publications
6
72
1
Order By: Relevance
“…Therefore, the bystander effect was independent of radiation dose delivered to the cell population. This result reinforces the finding that the microbeam-induced bystander effect in a confluent culture does not depend on the radiation dose and LET 18 and is also in agreement with other reports of the dose independence of the bystander effect induced by conditioned medium harvested from irradiated cells. 38 …”
Section: Dose Response Of Bystander Mn Inductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, the bystander effect was independent of radiation dose delivered to the cell population. This result reinforces the finding that the microbeam-induced bystander effect in a confluent culture does not depend on the radiation dose and LET 18 and is also in agreement with other reports of the dose independence of the bystander effect induced by conditioned medium harvested from irradiated cells. 38 …”
Section: Dose Response Of Bystander Mn Inductionsupporting
confidence: 93%
“…For confluent cell monolayers and 3-dimensional cell clusters, gap junctional intercellular communication (GJIC) has been found to play a critical role in radiation-induced bystander effects. [14][15][16][17][18] In other cases, soluble extracellular factors, including reactive oxygen species (ROS) and cytokines, [19][20][21] which are released from irradiated cells and even human tissue, 22 contribute to the bystander responses. We and others have found that radiation-induced nitric oxide (NO) has multiple bystander effects on non-irradiated cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(4,7,(9)(10)(11)(12)(13) Gap junctions are membrane channels that connect the cytoplasm of cells and allow direct exchange of small molecules and ions between adjacent cells. GJIC is essential for the maintenance of tissue homeostasis and proliferation and the regulation of embryonic development and differentiation, and it plays a key role in induction of the bystander effect.…”
mentioning
confidence: 99%
“…It has been proposed that the mediating mechanism involves secreted soluble factors, (4)(5)(6) an increase in oxidative stress, (7) plasma membrane-bound lipid rafts, (8) and gap junctional intracellular communication (GJIC). (4,7,(9)(10)(11)(12)(13) Gap junctions are membrane channels that connect the cytoplasm of cells and allow direct exchange of small molecules and ions between adjacent cells. GJIC is essential for the maintenance of tissue homeostasis and proliferation and the regulation of embryonic development and differentiation, and it plays a key role in induction of the bystander effect.…”
mentioning
confidence: 99%